Avaliação nutricional da torta de babaçu e sua utilização em dietas para frangos de corte Label Rouge - SILVA, Rubens Fausto da (2009)
Three research works were conducted in order to determine the chemical composition, nutrient and energy digestibility, apparent metabolizable energy (EMA) and apparent metabolizable energy corrected by nitrogen retention (EMAn) of babaçu cake, as well as to evaluate the results of its use on performance and carcass traits of Label Rouge chicks. The first experiment consisted a biological assay carried where the traditional total feces collection method was used to characterize babaçu cake bromatologically, as well as to determine its energy levels and metabolizability coefficients. Seventy two Label Rouge day-old-chicks where placed in metallic batteries and at the 14th day they where assigned to a randomized block design with two treatments and six replicates of 6 birds each. The results found where: Crude energy = 5,056 kcal/kg, Crude protein = 18.8%, Crude fiber = 29.50%, Ether extract = 8.8%, Calcium = 0.19%, Phosphorus = 0.67%, EMA= 2,650 kcal/kg and EMAn=2,580 kcal/kg. The dry matters, Crude energy s and ether extract s apparent coefficient of metabolizability were 31.72%; 46.78%; 92.35%, respectively. The nitrogen balance of reference diet and test diet where respectively 15.90% and 6.54%. The second research work was conducted aiming to evaluate the effect of different levels of inclusion of babaçu cake in diets based on corn and soybean meal on the performance of free range chickens from 1 to 7, 1 to 14, 1 to 21 and 1 to 28 days old. Three hundred day-old (male and female) Label Rouge chickens, were assigned to a completely randomized design with five treatments (0, 8, 16, 24 and 32% of inclusion of babaçu cake) and four replicates of 15 birds each. Inclusion levels of babaçu cake influenced feed intake at ages 1 to 7 days (P=0.0031) and did not influence other ages. Live weight and weight gain were influenced at age 1 to 7 days when it was used the SNK test for mean comparison. Live weight was affected at ages 1 to 14 (P=0.0003), 1 to 21 (P=0.0028) and 1 to 28 (P=0.0168) days old, as well as weight gain at ages 1 to 14 (P=0.0004), 1 to 21 (P=0.0037) and 1 to 28 (P=0.0196) days old. Feed convertion was affected at ages 1 to 7 (P≤0.0001) and 1 to 28 (P=0.0027).The third research work was aimed to evaluate the effect of different levels of inclusion of babaçu cake on performance, carcass yield and carcass protein and fat deposition of Label Rouge broiler chicks that received the experimental diets from 36 to 84 days old. Three hundred and sixty birds (male and female) were assigned to a completely randomized design with five treatments (0, 8, 16, 24 and 32% of inclusion of babaçu cake) and four replicates of 18 birds each. Weight at 84 days old and weight gain were not influenced by the different levels of babaçu cake, however feed intake increased (P= 0.002) and feed convertion was negatively affected (P=0.052) by crescent levels of babaçu cake in the diets. Carcass yield, carcass fat and protein deposition and abdominal fat deposition weren´t influenced as the inclusion levels of babaçu cake increased. It is possible the use of up to 32% of inclusion of babaçu cake in the diet of Label Rouge broiler chicks from 36 to 84 days old